SISTEM PENDUKUNG KEPUTUSAN DALAM MENENTUKAN JURUSAN DI SEKOLAH SMK NEGERI KOTA BATAM MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Yusmet, Ramos; Dasa Putri, Anggia (Computer Science and Industrial Engineering, 2025)
The selection of academic majors at vocational high schools (SMK), particularly at SMK Negeri 7 Batam, often faces challenges in aligning students’ preferences with their academic capabilities. This issue arises due to the current New Student Admission Selection (SPMB) system, which allows students to select three program options, yet only the first choice is prioritized, resulting in frequent mismatches in placement when competition is high. To resolve this, a web-based Decision Support System (DSS) is developed using the Simple Additive Weighting (SAW) method to evaluate and recommend suitable majors based on academic performance and student interest. The system is built with Visual Studio Code as the development environment, Laravel as the PHP framework, and Unified Modeling Language (UML) to design system workflows and structures. The decision-making process involves score normalization, criteria weighting, and ranking of alternatives to produce optimal recommendations. Accessible through a web browser, the system supports students, teachers, and admission committees by providing a more efficient and accurate tool for academic major placement. Testing results demonstrate the system’s effectiveness in improving decision accuracy and supporting academic guidance processes within the vocational school environment.